Literature Review: The Role of Women Entrepreneurs in the Digital Era - Sutedja, D A Gladysia Sistadanta Kurnia Dewi (JUSTBEST Journal of Sustainable Business and Management, 2026)
Women are expected to have the same gacor slot opportunities to develop as men, in reality, various forms of discrimination are still encountered. Women now face dual demands, namely fulfilling responsibilities as mothers and wives, while simultaneously playing an active role in the world of work. The digital era provides great opportunities for women to promote and market products in a more efficient manner. Women have great gacor slot potential in advancing the wheels of the economy, including entrepreneurial opportunities as a career choice for women to contribute to the economy and improve the welfare of themselves, their families, and the community. The method in this research is a literature review. Literature uses an academic database, namely Google Scholar. The development of women's entrepreneurship in East Java for the period 2020–2024 shows rapid progress with an increase in the proportion of women entrepreneurs to 68% in 2024.